Association between dry eye disease and depression: An umbrella review - Tsai, Ching-Yao; Jiesisibieke, Zhu Liduzi; Tung, Tao-Hsin (Frontiers in Public Health, 2022)
Purpose: This umbrella review aimed to summarize the available evidence on the association between dry eye disease and depression. Methods: We searched the Pubmed, Embase, and Cochrane databases using the search string “(Dry eye syndrome OR Keratoconjunctivitis sicca OR KCS OR Aqueous tear deficiency OR Sjogren syndrome) AND (depression OR depressive symptoms) AND (meta-analysis OR systematic review)” from inception to July 20, 2022. We considered all meta-analyses investigating the association between dry eye disease and depression. The protocol of this umbrella review was registered in the International Prospective Register of Systematic Reviews (PROSPERO ID: 320619). Results: After summarizing the included meta-analyses, it was concluded that dry eye disease is associated with depression. The symptoms of dry eye disease affect the daily lives of patients, thus affecting their mood. However, further evidence is required to confirm this association. Conclusion: This finding highlights the importance of psychological support for patients with dry eye disease. Future clinical studies should investigate the mechanism underlying the association between dry eye disease and depression.